Aktualne możliwości zmechanizowanego pozyskiwania drewna w warunkach górskich - Jodłowski, Krzysztof; Referowska-Chodak, Ewa; Kalinowski, Michał (Leśne Prace Badawcze, 2018)
Modern technologies allow wood harvest in almost all terrains, including hard-to-reach mountain areas. Each of the technical measures used, however, has limitations due to its construction and the nature of the work. The present study discusses issues related to the selection of machinery and technology as well as planning work in mountainous terrain, taking into account factors such as accessibility of the stand and terrain properties (slope, ground bearing capacity). Adaptive changes of forest machinery for work in mountain stands are also presented. This article furthermore discusses possibilities of applying machinery and technologies already used in other countries to harvest wood in mountainous forests in Poland.